26+27=-39x-6

Simple and best practice solution for 26+27=-39x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26+27=-39x-6 equation:


Simplifying
26 + 27 = -39x + -6

Combine like terms: 26 + 27 = 53
53 = -39x + -6

Reorder the terms:
53 = -6 + -39x

Solving
53 = -6 + -39x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '39x' to each side of the equation.
53 + 39x = -6 + -39x + 39x

Combine like terms: -39x + 39x = 0
53 + 39x = -6 + 0
53 + 39x = -6

Add '-53' to each side of the equation.
53 + -53 + 39x = -6 + -53

Combine like terms: 53 + -53 = 0
0 + 39x = -6 + -53
39x = -6 + -53

Combine like terms: -6 + -53 = -59
39x = -59

Divide each side by '39'.
x = -1.512820513

Simplifying
x = -1.512820513

See similar equations:

| -5b-6-3b= | | 15-(4m+-5)=32 | | 10x-30=9x+11 | | 8+3x=0.5(16+6x) | | 5x-35=-5 | | 3=9+5y | | 3x-18=85 | | 5v^7=8 | | -l=n+5 | | 3(x+2)=4x+1 | | n/3-2=18 | | 13=48-x | | (kx^2)+(2k+1)x+1=0 | | 60=5m+5 | | 1x+10-7x= | | 5g+21=21 | | 13y-5y=56 | | 64+36=4x | | Y=0.5(4)2+46 | | 9/10g=9/10 | | 6x+18=-26+26+6x | | 2x+1=5-2(2x-1) | | 0.5a=9 | | 3h(4-3q)=520 | | 2p-1/4=2/3/4 | | 7y^4+28y^3+28y^2= | | 9-(2p+5)=4p | | 2x+16=8x+40 | | 18m=-360 | | m-3/4=m/6 | | 1/2x-1/3=1/3 | | log(b)5=37 |

Equations solver categories